Clarifying the Impact of Electrode Material Heterogeneity on the Thermal Runaway Characteristics of Lithium‐Ion Batteries - Chenran Du; Kun Yan; Xueling Shen; Yi Cui; Xiaobing Li; Jingjing Li; Ran Xu; Xiaoli Ma; Qian Huang; Yanyan Fang; Hang Zhang (Advanced Energy & Sustainability Research)
The safety and efficiency of lithium‐ion batteries (LIBs) suggest a promising future for this technology, particularly in the automobile industry. However, thermal runaway—wherein a LIB undergoes an uncontrollable increase in temperature that may result in smoke, fire, or explosion—represents an important and widely studied failure type. Since the electrodes of LIBs are manufactured from porous composite materials, their heterogeneity can significantly influence the effective material characteristics and microscale behaviors of LIBs during operation. Microstructure geometric and electrochemical–thermal models are typically used to investigate these impacts. Herein, a microstructure geometric model is constructed of LIB's electrodes. A virtual multiphysics model is used to simulate the overcharging thermal runaway condition. The model's accuracy is validated through real‐world experiments. The model shows greater accuracy compared to the result from a conventional homogeneous geometric model and better reflects the heterogeneous internal phenomenon. The model is applied to a variable analysis in order to investigate how the varying heterogeneity of the cathode's porosity impacts the cell during overcharging thermal runaway behavior. Our results indicate that decreasing porosity heterogeneity at the cathode may delay thermal runaway, owing to the heterogeneous impact on particle diffusion behaviors and the side reaction rate.